One-pot RAFT and fast polymersomes assembly: a ‘beeline’ from monomers to drug-loaded nanovectors - Mastrotto, Francesca; Breen, Alastair; Sicilia, Giovanna; Johnstone, Alexander D.; Marsh, Georgina E.; Grainger-Boultby, Christine; Russell, Noah A.; Alexander, Cameron; Mantovani, Giuseppe (Royal Society of Chemistry, 2016)
Rapid and simple routes to functional polymersomes are increasingly needed to expand their clinical or industrial applications. Here we describe a novel strategy where polymersomes are prepared through an in-line process in just a few hours, starting from simple acrylate or acrylamide monomers. Using Perrier’s protocol, well-defined amphiphlic diblock copolymers formed from PEG acrylate (mPEGA₄₈₀), 2-(acryloyloxy)ethyl-3-chloro-4-hydroxybenzoate (ACH) or 2-(3-chloro-4-hydroxybenzamido)ethyl acrylate (CHB), have been synthesised by RAFT polymerisation in one-pot, pushing the monomer conversion for each block close to completion (≥94%). The reaction mixture, consisting of green biocompatible solvents (ethanol/water) have then been directly utilised to generate well-defined polymersomes, by simple cannulation into water or in a more automated process, by using a bespoke microfluidic device. Terbinafine and cyanocobalamine were used to demonstrate the suitability of the process to incorporate model hydrophobic and hydrophilic drugs, respectively. Vesicles size and morphology were characterised dy DLS, TEM, and AFM. In this work we show that materials and experimental conditions can be chosen to allow facile and rapid generation drug-loaded polymersomes, through a suitable in-line process, directly from acrylate or acrylamide monomer building blocks.